Ludwig’s angina – evaluation of its medical treatment in 47 cases - Sharma, V (Journal of College of Medical Sciences-Nepal, 2012)
This is a retrospective study of 47 cases suffering from Ludwig’s angina who received treatment at Manipal Teaching Hospital, Pokhara, between March 2005 and December 2010. Objective of this study was to compare the treatment efficacy of two intravenous antibiotic regimens for the treatment of Ludwig’s angina.27 cases who received crystalline Penicillin G +Metronidazole were placed in group A, while 20 patients who received Ceftriaxone + Clindamycin were placed in group B. The efficacy results based on the disease progressing to abscess formation were analyzed. Journal of College of Medical Sciences-Nepal, 2011, Vol-7, No-3, 1-5 DOI: http://dx.doi.org/10.3126/jcmsn.v7i3.6689